Effects of Soil Type and Different Pre-sowing Treatments on Seedling Emergence and Vigour of Acacia sieberana - Pahla, Innocent; Muziri, Tavagwisa; Chinyise, Tiniel; Muzemu, Simbarashe; Chitamba, James (Scientific & Academic Publishing, 2022)
An experiment was carried out at Midlands State University to determine the effect of soil type and different seed treatments on seed emergence and seedling vigour of Acacia sieberana. The experiment was arranged as a 2×5 factorial treatment structure laid out in a completely randomized design with three replications. Soil type had two levels (sand and clay) while seed treatments had five levels (98% H2SO4 for 60 minutes, 98% H2SO4 for 90 minutes, hot water only, hot and cold water, and straight sowing (control)). Results showed that soil type and seed treatment significantly affected seed emergence (p<0.05) of A. sieberana. Seeds subjected to 98% H2SO4 for 60 minutes and then sown in sand soil gave the highest emergence percentage of 80%, followed by those that were hot water treated and sown in sand soil with 53%. Soil type and seed treatment significantly affected days to emergence (p<0.05) of the A. sieberana. Seeds treated with 98% H2SO4 for 60 minutes and then sown in sand soil had the shortest period to emergence (6 days). Straight sown seeds recorded the longest time to emergence (18 days). It was concluded that subjecting seeds to 98% H2SO4 for 60 minutes and sowing them in sandy soils can improve emergence percentage and also reduce time taken to emergence of A. sieberanaseeds.